Controlled Sulfurization of Ag Nanorod into Ag‐Ag2S Hetero‐Nanorod. (24th May 2021) - Ha, Taeyong; Bang, Gyuhyun; Kwon, Yongju; Kim, Sungjee; Jeong, Sanghwa
Abstract : Silver‐silver sulfide hetero‐nanorods (Ag‐Ag2 S HNRs) were prepared by controlled sulfurization of colloidal silver nanorods in solution. Intermediate Ag‐Ag2 S HNRs were observed during the sulfurization by electron microscopy and absorption spectroscopy. Intermediate Ag‐Ag2 S HNR showed higher photocatalytic efficiency than initial Ag NR. ​